Nursing Care Knowledge Management Based Training Decrease Nosocomial Infection Inciden in Post Sectio Cesarea Patients - Ahsan Ahsan; Nursalam Nursalam; Nyoman Anita Damayanti (Universitas Airlangga, 2013)
Introduction: Model of nursing care based on knowledge management can reduce the incidence of nosocomial infections through the performance of nurses in the prevention of infection. Nursing care based on knowledge management is established from identi fi cation knowledge which is required, prevention performance of nosocomial infections post caesarean section. Nosocomial infections component consists of wound culture result.Method: This study was an observational study with a quasy experimental design. The population were all of nursing staff who working in obstetrics installation and a number of patients who is treated in hospitals A and B post sectio caesarea. Sample is comparised a total population all the nursing staff who worked in obstetrics installation according to criteria of the sample, and most of patients were taken care by nursing staff post caesarean section which is taken by random sampling 15 patients. Data was collected through observation sheets and examination of the wound culture. Data analysis which is used the t test. Result: The result was showed that there was signi fi cant difference in the incidence of nosocomial infection in patients with post sesctio caesarea in hospital before and after nursing care training based on knowledge management (tvalue = 2.316 and p = 0.028 < α = 0.05 level), and the incidence of nosocomial infection was lower after training than before training.Discussion: It can be concluded that training knowledge management based on nursing care effectives to reduce Incidence of Nosocomial Infections in Patients after Sectio Caesarea.